Laṭāʾif al-amthāl wa-ṭarāʾif al-aqwāl : Sharḥ-i Fārsi-yi 281 mathal-i ʿArabī - Waṭwāṭ, Rashīd al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
Born into a family that traced its origins to caliph ʿUmar b. al-Khaṭṭāb (d. 23/644), Rashīd al-Dīn Waṭwāṭ (d. 578/1182) was a graduate of the Niẓāmiyya academy in his hometown of Balkh, where he had received a solid grounding in Arabic language and literature. Bi-lingual in Persian and Arabic and an accomplished writer of poetry and prose, he spent the greater part of his active life in Gurgānj, steadily climbing the administrative ranks to become chief-secretary at the courts of Qizil Arslan Atsiz Khwārazmshāh (d. 551/1156) and his son Il-Arslan b. Atsiz (d. 568/1172). Bald, small sized and bad-tempered, Rashīd al-Dīn used his sharp tongue to protect himself from ridicule and animosity. He is mostly known for his annotated translation of 100 sayings of ʿAlī b. Abī Ṭālib and several collections of letters. The Persian renderings of 281 Arabic sayings and proverbs presented here offer an excellent sample of the author's taste and erudition.